The language aspects of Chinese papercuts / Florence Kuek Chee Wee - Kuek, Florence Chee Wee (UPENA, 2006)
A recent archeological excavation in Yutian County of Xinjiang has brought to the world one of the oldest form of Chinese Papercuts in the shape of a rosette. Its history can be traced as far back to the period known as the Northern and Southern Dynasties (386-581 A.D.) Nonetheless, Chinese paper cutting is an age-old handicraft of the Chinese people. One can easily detect thousands of themes and patterns presented in this type of simple, two-dimensional cuttings. Furthermore, one can detect that some Chinese characters or phrases are always presented in the Chinese papercuts. Thus, the Chinese papercuts can be examined as items that have captured the blueprints of Chinese culture, especially in the aspect of Chinese language. This short article seeks to help us examine the rich spectrum of the 'expressed languages' embedded in the Chinese papercuts.